Key drivers structuring rotifer communities in ponds: insights into an agricultural landscape. (6th May 2021) - Onandia, Gabriela; Maassen, Sebastian; Musseau, Camille L; Berger, Stella A; Olmo, Carla; Jeschke, Jonathan M; Lischeid, Gunnar
Abstract: Understanding the influence of environmental and spatial factors on the structure of aquatic communities remains a major challenge in community ecology. This study aims to identify main drivers of rotifer abundance and diversity in ponds embedded in an intensive agricultural landscape in Northeast Germany. We studied 42 ponds of glacial origin (kettle holes) covering a wide range of environmental parameters. The predominant factors structuring the rotifer metacommunity shifted from abiotic environmental filtering in spring to unstudied factors in autumn, while spatial factors remained less important. Fertilizer-driven salinization, internal nutrient recycling, primary productivity and sediment phosphorus release were the prevalent biogeochemical processes in the ponds. Both fertilizer-driven salinization and primary productivity negatively affected rotifer alpha diversity, and positively affected beta diversity. This impact was lower in forest ponds than in those surrounded by arable fields or grassland. However, rotifer diversity did not significantly differ among land-use categories. Our results indicate that the long-term impact of intensive agriculture in the region and the associated widespread eutrophication overrides the direct influence of land use on rotifer diversity but point to an indirect effect via fertilizer-driven salinization. Furthermore, this study highlights the role of ponds in enhancing regional biodiversity in agricultural landscapes.